Alkaloids bearing rare skeletons from Forsythia suspensa with anti-inflammatory and anti-viral activities in vitro. (June 2021) - Zhao, Lin; Li, Wei; Dai, Sheng-Jun; Liu, Rong-Xia; Xie, Ze-Ping; Zhang, Shu-Min; Yue, Xi-Dian
Abstract: Five alkaloids, including two previously undescribed alkaloids, named forsyshiyanines A and B, attributable to the rare skeletons 4b, 5, 6, 7, 8, 8a, 9, 10-octahydrobenzo[ f ]quinoline and (6, 7-dihydro-5 H -cyclopenta[ c ]pyridin-7-yl)methyl, respectively, along with three known ones (3 –5 ), were isolated from the ripe fruits of Forsythia suspensa . The chemical structures including absolute configurations of two undescribed compounds were established using integrated spectroscopic techniques, electronic circular dichroism calculations, and single-crystal x-ray diffraction analysis. In vitro, five alkaloids showed anti-inflammatory activities, with the inhibition rates of the release of β -glucuronidase from polymorphonuclear leukocytes of rats being in the range 47.9%–56.0% at a concentration of 10 μ M. Moreover, five compounds exhibited anti-viral activities against influenza A virus and respiratory syncytial virus, with IC50 values in the range of 7.3–32.5 μM and EC50 values in the range 3.7–14.1 μM. Graphical abstract: The fruit of Forsythia suspensa is a traditional Chinese medicine with good anti-inflammatory and anti-viral activities. Image 1 Highlights: Two undescribed alkaloids were isolated from the fruits of Forsythia suspensa. The absolute configurations of two undescribed alkaloids were determined. Five alkaloids showed significant anti-inflammatory activities. Five alkaloids showed anti-viral activities against the H1N1 virus and RSV.